Innovativeness and network competence : an integration and empirical examination - Rodrigues, Cristina S. (2006)
This paper reports a study of the interdependence of network competence and innovativeness in a product innovation context. Based on a systematic review on innovation literature, authors define two review constructs for innovativeness and network competence. The dimensions of both concepts were validated through a sample of 164 manufacturing Portuguese firms, which provides interesting results concerning the behavior of Portuguese manufacturing companies at the level of network innovation.